1994
DOI: 10.1021/jm00033a005
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalin Analogs as Systemically Active Antinociceptive Agents: O- and N-Alkylated Derivatives of the Dipeptide Amide L-2,6-Dimethyltyrosyl-N-(3-phenylpropyl)-D-alaninamide

Abstract: A number of O- and N-alkylated derivatives of the antinociceptive, orally active, mu-opioid-selective truncated enkephalin analog L-2,6-dimethyltyrosyl-N-(3-phenylpropyl)-D-alaninamide (2, SC-39566) were synthesized to explore the structure-activity relationships of the series. The parent molecule is quite forgiving of substitution on the tyrosyl phenolic moiety and on the alanyl nitrogen. The tyrosyl and (phenylpropyl)amide NH sites, however, appear to be critical to interactions with the receptor, for even m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The development of a unique analogue of Tyr, achieved through methylation of the 2′ and 6′ positions of the tyramine ring to yield Dmt49 paved the way for realizing increased bioactivities in small opioid dipeptides. Whereas some substitutions of Dmt into [2‐ D ‐penicillamine, 5‐ D ‐penicillamine]‐enkephalin (DPDPE) and Dmt‐ N ‐(3‐phenylpropyl)‐ D ‐alaninamide did not yield dramatic results,50–53 the incorporation of Dmt into H–Tyr–Tic–OH increased δ‐receptor affinity 8500‐fold 54. This finding revolutionized the opioid field by clearly demonstrating that a single amino acid residue can have monumental effects on the opioid receptor affinity and bioactivity and firmly established the Dmt–Tic pharmacophore (Figure 1) as a new template for opioid ligand design 54, 55…”
Section: Introductionmentioning
confidence: 99%
“…The development of a unique analogue of Tyr, achieved through methylation of the 2′ and 6′ positions of the tyramine ring to yield Dmt49 paved the way for realizing increased bioactivities in small opioid dipeptides. Whereas some substitutions of Dmt into [2‐ D ‐penicillamine, 5‐ D ‐penicillamine]‐enkephalin (DPDPE) and Dmt‐ N ‐(3‐phenylpropyl)‐ D ‐alaninamide did not yield dramatic results,50–53 the incorporation of Dmt into H–Tyr–Tic–OH increased δ‐receptor affinity 8500‐fold 54. This finding revolutionized the opioid field by clearly demonstrating that a single amino acid residue can have monumental effects on the opioid receptor affinity and bioactivity and firmly established the Dmt–Tic pharmacophore (Figure 1) as a new template for opioid ligand design 54, 55…”
Section: Introductionmentioning
confidence: 99%
“…Recent structure-activity studies have shown that introduction of the artificial amino acid 2Ј,6Ј-dimethyltyrosine (Dmt) in place of the N-terminal Tyr residue is a promising way to greatly enhance receptor affinity and functional potency. [2][3][4][5][6][7][8][9][10][11][12][13] However the Dmt 1 -substitution generally has resulted in low receptor selectivity due to markedly enhanced affinity toward the concomitant receptor vs. the preferred receptor. 3,6,8,12,13) We have recently demonstrated that 2Ј,6Ј-dimethylphenylalanine (Dmp) is an excellent surrogate for the Phe at position 3 in Tyr-D-Arg-Phe-bAla-NH 2 (YRFB), 14) endomorphin 2, 15) dermorphin, 16) and deltorphin II.…”
mentioning
confidence: 99%
“…Later alterations in opioid structure, in particular the substitution of the N-terminal residue Tyr by Dmt (Chandrakumar et al, 1992;Hansen et al, 1992;Pitzele et al, 1994;Guerrini et al, 1996;Salvadori et al, 1997;Sasaki et al, 1999;Schiller et al, 2000;Bryant et al, 2003) and dimerization of Dmt through alkyldiamine , led to increases in the binding to opioid receptors and bioactivities in vitro and in vivo (Bryant et al, 2003). This study provided evidence that a pyrazinone ring connecting to two symmetric Dmt N termini by alkyl chains might serve a dual role in opioid peptides as both message and address domains.…”
Section: Discussionmentioning
confidence: 76%
“…Message and address domains of opioid peptides represent distinct starting points for the design and development of novel opioid mimetics. For example, studies on opioid peptides showed that the substitution of the N-terminal tyrosine by 2Ј,6Ј-dimethyl-L-tyrosine (Dmt) dramatically increased receptor affinity in numerous peptides and enhanced their antinociceptive effect (Chandrakumar et al, 1992;Hansen et al, 1992;Pitzele et al, 1994;Guerrini et al, 1996;Sasaki et al, 1999;Schiller et al, 2000;Bryant et al, 2003). Moreover, Dmt played a key role in the formation of the Dmt-Tic pharmacophore family of potent ␦-opioid receptor antagonists (Salvadori et al, 1997;Bryant et al, 1998, which were transformed into potent ␦-opioid receptor agonists by subtle changes in the C-terminal link to a third aromatic nucleus (Balboni et al, 2002).…”
mentioning
confidence: 99%